Igbo Tortoise Trickster Tales as Agents of Immoral Behaviour in Our Society: A Utilitarian Theoretic Approach - Onu, John Odo; Onuh, Esther Chidimma (NIU Journal of Humanities, 2026)
African folktales are primarily narrated to teach moral lessons, reprimand inappropriate behaviour, and Caution against immorality in African Society. Nevertheless, Igbo tortoise folktales do not seem to serve these functions. Instead, the tortoise in these folktales frequently exhibit behaviour that contravenes moral standards and is associated with immorality without any unpleasant consequences or punishment. The objectives of this study are to explore behaviour themes commonly associated with immorality as depicted by the Tortoise Character in Igbo folktales. The study also explores the moral degeneration phenomenon as portrayed in folktales and in society. Mbe (tortoise) and the modern-day occurrences of moral decadence are reported in digital media including radio, television and newspapers on daily basis. The Study is a qualitative research. The Study is anchored on Utilitarian theory of psychology to determine the extent to which tortoise folktales contravenes the notion of morality and the the function of of teaching moral precepts. The primary source of data Collection includes the moral precepts. The primary source of data collection includes the folktales collected from the Book of Igbo Folktales. The Secondary Sources of data Collection includes journal articles, and dissertations on African folktales. The findings of the study reveal that most Igbo tortoise folktales depict behaviours associated with immorality and as such its effectiveness in teaching about morality becomes compromised and flared. The behavioral theme of trick, violence, jealousy, murder and so on are abound in Igbo tortoise trickster tales. Keywords: Trick, folktale, morality, immorality, Children and behaviour.